The relationship between personality traits and affect with students’ adaptation to student life during the COVID-19 pandemic - Čuljak, Lora; Pravica, Maja; Butković, Ana (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Transition to higher education is stressful for many students, and the success of adaptation to college is related to personality traits and affective experience. Also, the COVID-19 pandemic has brought changes to everyday life and the learning environment. The aim of this study was to examine the contribution of personality traits and affective experience in explaining adaptation to college among first-year students during the COVID-19 pandemic. The research was conducted on students (N = 119) in Croatia who were in their first year of studies during the pandemic. Participants filled in the Big Five Inventory–2 Short Form, Student Adaptation to College Questionnaire and the Croatian adaptation of the short form of the Positive and Negative Affect Schedule. Results showed that personality traits and affective experience were significant predictors of adaptation to college, explaining 50% of the academic adjustment variance, 46% of the emotional adjustment variance and 40% of the social adjustment variance. Students who experienced more positive affect had better academic adjustment, those who experienced less negative affect had better emotional adjustment, while students with higher extraversion and those who experienced more positive affect had better social adjustment. Results of this study confirm the importance of individual characteristics in adaptation to college during the pandemic.